African solutions to African problems: a narrative of corruption in postcolonial Africa - Nkosingiphile Mkhize; Sobongile Moyo; Sipho Mahoa (Cogent Social Sciences)
This article assesses the philosophical orientation of ‘African solutions to African problems’ in the fight against corruption in post-colonial Africa. It investigates this narrative that is often used in the context of peace and security in Africa – to test whether there is an element of uniqueness in measures to fight corruption on this continent. The study seeks to broadly address the following questions: How do Ubuntu and other African traditions reinforce different conceptions of what corruption, and nepotism, are and how they should be dealt with; Is Africa unique? Why can a generic definition of corruption not be adopted like those of democracy, capitalism, and socialism, and generic strategies to counter this problem not be adopted like for other societal and political issues? The concept of ‘African solutions to African problems’ has been extensively debated in the context of tackling different challenges, such as corruption, in Africa. This concept underscores the imperative for African nations to assume the forefront in identifying and executing remedies for their distinct challenges, rather than depending on external interventions or recommendations. In the context of anti-corruption in Africa, this narrative could lead to misleading and unwanted further weakening of state institutions and policies because these would be viewed as being non-African. The narrative of African Solutions to African Problems is associated with Pan-Africanism, universalism, and exceptionalism. The article adopted a qualitative methodological approach based on the analysis and assessment of secondary data in the literature to understand this pre-existing phenomenon of corruption and anti-corruption in post-colonial Africa. An exploratory qualitative secondary literature review of global and African sources on corruption and anti-corruption strategies. This methodological approach contributed toward a better understanding of the usefulness and relevance of the narrative ‘African solutions to African problems’ in combatting corruption in post-colonial Africa. The research findings include that the widespread corruption in governments throughout Africa has its origins in long-standing cultural and political traditions centered on patronage and is often aggravated by a political attitude of strong entitlement. Implementing the notion of African solutions to African problems within the framework of corruption in postcolonial Africa is a challenging and enduring undertaking. A collaborative endeavor including governments, civil society, the commercial sector, and the international community is necessary. Adapting techniques to the distinct difficulties and circumstances of specific nations is essential for advancing the fight against corruption.